Structural adjustment or a sustainable future? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Rice Cultivation in the Farming Systems of Sukumaland, Tanzania. A Quest for Sustainable Production under Structural Adjustment Programmes.